Analisis Faktor Penyebab Minat Kuliah pada Perguruan Tinggi Islam - Latifah Latifah; Ahmadi Ahmadi (Medan Resource Center, 2023)
In the pursuit of educational development, the youth of Pakamban Laok Village in Pragaan Subdistrict show a strong preference for pursuing higher education at Islamic institutions affiliated with Islamic boarding schools. This growing interest among the youth of Pakamban Laok serves as a foundation for self-development in the realm of education. This study aims to identify and gather data on the internal and external factors influencing the inclination to study at the Islamic College of Pakamban Laok Village in Pragaan District, Sumenep Regency. Employing a qualitative descriptive research method, data and information were collected and subsequently analyzed to address the objectives of this study. The findings reveal that internal factors, such as motivation, aspirations, and hopes, significantly influence the interest in learning at the Youth Islamic Boarding School in Pakamban Laok Village, Pragaan Sumenep District. External factors, including family, friends, school, and religious practices, also play a significant role in shaping the interest in learning among adolescents attending Madrasah Ibtidaiyah Pakamban Laok Village, Pragaan Sumenep District.